(untitled) (Research, Society and Development, 2022)
The tropical Field expansion are closely related to input consumption, which may impact negatively on economy, even more in particular circumstances as the actual pandemic situation. The aim of this study was to evaluate the agronomic efficiency of the soil remineralizer from Araxá geologic group´s micaxiste (Bela Vista de Goiás village, Goiás, Brazil). This study was conducted on Escola de Agronomia of the Universidade Federal de Goiás, in Goiânia, Goiás, at hoop house using two different soils: Latosol Red distrofic clayey and Latosol Red-Yellow distrofic half texture. The experiment was planned with full factorial design by KVB-K doses (0.0, 30.0, 60.0, 120.0 and 240.0 kg ha-1 K2O). Two commercial products were used as reference (FMX – from Ministério da Agricultura, Pecuária e Abastecimento – MAPA, as the natural source; and Potassium Chloride), both in 60 kg ha-1. Then, after the pots (9 kg) were prepared and the soybean and millet were distributed in succession. Agronomic efficiency was calculated according potassium content in the parts of the system (soil and plant), and productivity of both cultures. The equations were also considered the commercial reference to FMX and KCl. Data are demonstrated high agronomic efficiency from FMX to all treatments. Compared to KCl, to equivalence in crop production, the KVB-K needs high inputs, especially with more soluble sources. Results shown high potential from micaxiste on the system proposed.